The Influence of Culture on Impulse Buying Behavior: A Systematic Literature Review - Abu Bashar; Shalini Singh; Vivek Kumar Pathak (BBR: Brazilian Business Review, 2023)
Culture plays a significant buying role in shaping different aspects of consumer behavior such as rational, impulse, and compulsive buying behavior. Impulse buying is one of the prevalent phenomena that significantly affect the sales revenue of companies. This study focuses on unveiling the interaction between cultural factors and impulse buying behavior. For this systematic literature review, 112 significant articles were examined to understand the relationship between various aspects of culture and impulse buying behavior in both online and offline contexts. Further investigation of impulse buying in cross-cultural context helps to understand and classify different theoretical perspectives to study impulse buying behavior and cultural factors. This study offers practical implications for retail professionals and e-commerce strategists to design and implement viable cross-cultural marketing campaigns. Academic researchers may also understand research gaps and contribute further to understanding cross-cultural impulse buying.